Local Disorder and the Success of Firms in Residential Neighbourhoods - Mollenhorst, Gerald; Schutjens, Veronique (European Spatial Research and Policy, 2017)
According to economic geography literature, the success of firms is affected by the local context, in particular when firms are socio-spatially embedded. We expect this effect to be stronger when firms face an increase in local disorder. We analysed data on 344 firms (active in retail, eating and drinking establishments, personal services and private education, business services, cultural activities, manufacturing and building) in 108 Dutch residential neighbourhoods, and data on the changes in social and physical disorder of those neighbourhoods, to examine firm success determinants. We find that it is not the degree of disorder that matters to local firms turnover, but rather recent changes in local disorder. More in particular, we find that local firm turnover is negatively affected by an increase in local disorder, but only when a firm depends on daily visits from predominantly local customers. Our results suggest that physical and social local interventions to create safe and clean public spaces will indirectly positively influence local firms and subsequently, the neighbourhood economy. This spill-over effect is promising for both residents, who benefit from local amenities and local ‘buzz’, and local entrepreneurs, whose firm success is stimulated.